Polarization state and image rotation via spontaneously generated coherence in a spinning fast light medium. (27th October 2020) - Rahman, Habibur; Khan, Mansoor; Ahmad, Shabir; Tayyab, Muhammad; Bibi, Haseena; Ali, Hazrat
Abstract: In this article we propose a four-level rubidium (Rb 87 ) atomic system for observing interesting features of polarization state rotation in a fast light medium. We investigate spontaneously generated coherence (SGC) for a spinning medium. We show how SGC can affect different spectral profiles of the polarization state and images in this suggested model. We observe a 0.5 radian rotation and 2.5 microsecond time advancement in our proposed system. Our precise results will provide a new platform for researchers in quantum optics due to its applications in image coding, telecommunications and cloaking technology.